New Trends in Database and Information Systems II Selected papers of the 18th East European Conference on Advances in Databases and Information Systems and Associated Satellite Events, ADBIS 2014 Ohrid, Macedonia, September 7-10, 2014 Proceedings II - Bassiliades, Nick.; Bassiliades, Nick.; Ivanovic, Mirjana.; Ivanovic, Mirjana.; Kon-Popovska, Margita.; Kon-Popovska, Margita.; Manolopoulos, Yannis.; Manolopoulos, Yannis.; Palpanas, Themis.; Palpanas, Themis.; Trajcevski, Goce.; Trajcevski, Goce.; et al. (Advances in Intelligent Systems and Computing,, 2015)
This volume contains the papers of 3 workshops and the doctoral consortium, which are organized in the framework of the 18th East-European Conference on Advances in Databases and Information Systems (ADBIS’2014). The 3rd International Workshop on GPUs in Databases (GID’2014) is devoted to subjects related to utilization of Graphics Processing Units in database environments. The use of GPUs in databases has not yet received enough attention from the database community. The intention of the GID workshop is to provide a discussion on popularizing the GPUs and providing a forum for discussion with respect to the GID’s research ideas and their potential to achieve high speedups in many database applications. The 3rd International Workshop on Ontologies Meet Advanced Information Systems (OAIS’2014) has a twofold objective to present: new and challenging issues in the contribution of ontologies for designing high quality information systems, and new research and technological developments which use ontologies all over the life cycle of information systems. The 1st International Workshop on Technologies for Quality Management in Challenging Applications (TQMCA’2014) focuses on quality management and its importance in new fields such as big data, crowd-sourcing, and stream databases. The Workshop has addressed the need to develop novel approaches and technologies, and to entirely integrate quality management into information system management.  .